2007
DOI: 10.1364/ao.46.002361
|View full text |Cite
|
Sign up to set email alerts
|

Metallic film optimization in a surface plasmon resonance biosensor by the extended Rouard method

Abstract: The extended Rouard method is applied to the computation of a multi-absorbing-layer system for the optimization of surface plasmon resonance (SPR) sensors. Specifically, the effect of the properties of a metallic layer on the shape of the reflectivity and sensitivity curve is demonstrated in the case of a Kretschmann configuration. This theoretical investigation allows us to establish the best optical properties of the metal to obtain a localized SPR, given the illuminating beam properties. Toward the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…It defi nes the maximum dynamic and shape of the plasmon [7,33]. Figure 2 shows the calculated results as a series of SPR curves for silver thickness increasing in steps of 10 nm changing from 10 nm to 100 nm.…”
Section: Effect Of Fi Lm Thickness On the Spr-sensormentioning
confidence: 99%
See 2 more Smart Citations
“…It defi nes the maximum dynamic and shape of the plasmon [7,33]. Figure 2 shows the calculated results as a series of SPR curves for silver thickness increasing in steps of 10 nm changing from 10 nm to 100 nm.…”
Section: Effect Of Fi Lm Thickness On the Spr-sensormentioning
confidence: 99%
“…Furthermore, it was found that the variation in metal thickness decreases the amplitude of the resonance peak, which means a reduction in the transfer of incident energy to surface plasmons. The optimization of the thickness of the metal is important to work in the best coupling conditions and have the best sensitivity of the SPR sensor [7,33].…”
Section: Effect Of Fi Lm Thickness On the Spr-sensormentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, a much better resolution and higher-precision sensor can be produced by using the double-layer arrangement in comparison to the single-layer profile. The influence of using double metallic film on the sensitivity and stability of the sensor was also investigated by Lecaruyer and coworkers [49]. Since silver, and similarly gold, has poor adherence with glass; therefore chromium or titanium must be inserted to fix the silver or gold layer to the glass substrate.…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…The reflectivity minimum that can be reached depends on the thickness of the metal layer [54]. It is a compromise between the penetration depth of the optical wave and the excitation of the surface plasmons.…”
Section: Instrumental Methods Of Analysis-the Biochip Readermentioning
confidence: 99%